The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.5216/cab.v11i3.6123
|View full text |Cite
|
Sign up to set email alerts
|

EFEITO DO DIÂMETRO FOLICULAR SOBRE A QUALIDADE DOS OÓCITOS OBTIDOS DE OVÁRIOS DE OVELHAS (Ovis aries) E CABRAS (Capra hircus)

Abstract: Efeito do diâmetro folicular sobre a qualidade dos oócitos obtidos de ovários de ovelhas ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Previous studies have shown that body condition score, physiological conditions of the egg donor, breed, age and individual variations directly interfere with the quality of the recovered COCs (Edwards and Hansen, 1996;Vinoles et al, 2002;Fatehi et al, 2005;Cecconi et al, 2007). In addition, the absence of significant variation in the photoperiod throughout the year, the low rainfall, or even the high temperatures in equatorial or tropical zones, may cause a reduction in the quality of goat COCs (Jordan, 2003;Chaves et al, 2010Chaves et al, , 2011. According to Roth and Hansen (2004), inter-and intra-cellular components define how an oocyte will react to effects from the environment and high temperatures, even if within physiological ranges, potentially even being a stimulus to apoptosis in mammalian oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that body condition score, physiological conditions of the egg donor, breed, age and individual variations directly interfere with the quality of the recovered COCs (Edwards and Hansen, 1996;Vinoles et al, 2002;Fatehi et al, 2005;Cecconi et al, 2007). In addition, the absence of significant variation in the photoperiod throughout the year, the low rainfall, or even the high temperatures in equatorial or tropical zones, may cause a reduction in the quality of goat COCs (Jordan, 2003;Chaves et al, 2010Chaves et al, , 2011. According to Roth and Hansen (2004), inter-and intra-cellular components define how an oocyte will react to effects from the environment and high temperatures, even if within physiological ranges, potentially even being a stimulus to apoptosis in mammalian oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Even though goats are generally considered more adaptable to adverse conditions than other domestic animals, high temperatures and low rainfall also affect this species through the lack of good quality food, excessive temperatures, and the presence of toxic plants, among other factors to which the animals are constantly exposed to (Carneiro, 2008;Chaves et al, 2011). As a consequence, an overall decrease in reproductive efficiency may occur (Chaves et al, 2010(Chaves et al, , 2011, which can make the production of a cloned animal even more challenging. The adjustment of SCNT cloning procedures in goats, therefore, gains crucial importance in this specific environment, given that no reports of cloned goats produced in Brazil and between parallels 30 o N and 30 o S in the world have been available prior to this study and to our previous recent report (Martins et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As médias dos CCOs com qualidade QI e QII apresentando cumulus compacto com mais de três camadas de células foi pequena quando comparadas com os de qualidade QIII e QIV, como encontrado por CHAVES et al (2010). Esses autores concluíram que o diâmetro folicular não exerce influência sobre a qualidade dos CCOs recuperados de fêmeas caprinas, o que aumenta a importância das células do cumulus.…”
Section: Discussionunclassified